STYLISH CHARACTERISTICS OF THE LYRICS OF THE POET B.GENZHEMURATOV (TAMADDUN NURI JURNALI, 2024)
The article talks about the unique stylistic features of the poet B.Genjemuratov’s lyrics. The poet deepens his thoughts by skillfully using the free form and verlibre elements, as a result of which the work appears in a new style. The flow of thought in his works is sharper than one another, deeper in meaning than one another, and some of them are very serious from a socio-philosophical point of view. The poet's poems enrich our lyrics artistically with their unique syntactic structure, phonetic, lexical features.